2012
DOI: 10.1242/dmm.009696
|View full text |Cite
|
Sign up to set email alerts
|

Partial promoter substitutions generating transcriptional sentinels of diverse signaling pathways in embryonic stem cells and mice

Abstract: SUMMARYExtracellular signals in development, physiology, homeostasis and disease often act by regulating transcription. Herein we describe a general method and specific resources for determining where and when such signaling occurs in live animals and for systematically comparing the timing and extent of different signals in different cellular contexts. We used recombinase-mediated cassette exchange (RMCE) to test the effect of successively deleting conserved genomic regions of the ubiquitously active Rosa26 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…The observation that EBs can form multiple contact loci or an entire cap contact locus when confined in micropools raised the question whether the potential to express Bry is limited to specific areas on the outer layer of the EB, to the entire shell, or is uniform throughout the EB volume. Growing EBs in hanging drops, we first confirmed that a canonical Wnt activation reporter (SuTOP-CFP, [21]) showed co-localization with Bry, in agreement with observations that Bry is activated via the canonical Wnt pathway ( Fig. 2A) [9,22].…”
Section: Brachyury Competent Shell Is Formed Prior To Onsetsupporting
confidence: 87%
“…The observation that EBs can form multiple contact loci or an entire cap contact locus when confined in micropools raised the question whether the potential to express Bry is limited to specific areas on the outer layer of the EB, to the entire shell, or is uniform throughout the EB volume. Growing EBs in hanging drops, we first confirmed that a canonical Wnt activation reporter (SuTOP-CFP, [21]) showed co-localization with Bry, in agreement with observations that Bry is activated via the canonical Wnt pathway ( Fig. 2A) [9,22].…”
Section: Brachyury Competent Shell Is Formed Prior To Onsetsupporting
confidence: 87%
“…) (Srinivas et al, 2001), Gt(ROSA)26Sor tm2Mgn (ROSA26 mCherry ) , ROSA26 228.3TF [unpublished, contains a ʻ−228' deletion of the ROSA26 promoter similar to that described by Serup et al (2012)] and Setd5…”
Section: Lslyfpmentioning
confidence: 96%
“…Please click here to view a larger version of this figure. 19,22,27,30,[36][37][38][39][40] have been characterized for the formation of aggregates and, although subtle differences between cell lines are expected and have been observed, all the above lines show similar dynamics in terms of elongation and morphology. In terms of gene expression, the expression pattern is specific to the gene expressed, but within each cell line, the expression pattern is generally consistent over a number of passages.…”
Section: Aggregate Imaging and Quantitative Image Analysismentioning
confidence: 99%